Sliding-mode-based disturbance observer approaches for vehicle steering control. (1st January 2013) - Demirci, Murat; Gokasan, Metin
Disturbance observer estimates a disturbance on the control input channel by using past measurements instead of estimating the disturbance itself and is a very powerful method to improve vehicle motion dynamics. This study proposes two new disturbance observer approaches for vehicle steering control, which are based on Sliding Mode Control (SMC) theory. The controllers estimate the equivalent input extended-disturbance in the control input channel. The extended-disturbance includes modelling and parameter uncertainties of the vehicle in addition to external yaw disturbances caused by side wind, µ-split braking, etc., The steering controllers have been tested on a Fiat Doblo Van modelled in CarSim environment. The sliding-mode-based disturbance observer approaches developed in this work are the first known applications to vehicle steering control. The performances of the proposed vehicle steering control systems have been compared with the performances of the Inverse-Model-based Disturbance Observer (IMDO) approach, which is a well-known disturbance observer method for motion control.